Radiotherapy from C.B.P. - Torres, Miguel (Cirugía del Uruguay, 1982)
The role of Rt. in the treatment of lung cancer is still being discussed. The results obtained with it are generally believed to be poor. Rt can control primary and regional spread and it can be used exclusively as radical or palliative therapy or combined with surgery. Those topics are defined and discussed. The advancement in radiobiology will allow to improve results.